Mediação, conflito e cidade: uma análise dos limites e possibilidades do artigo 565 do CPC/2015 à luz do direito à moradia - Jessica Luiza Moreira Barbosa (2018)
This work sought to identify whether (and, if so, under what conditions) mandatory mediation of collective land conflicts, as proposed in article 565 of the Code of Civil Procedure / 2015, emerges as an instrument able to manage collective urban land conflicts (considering their social, economic and political aspects), in order to ensure and promote the right to housing. This work begins with considerations about the conflict, as a normal phenomenon in social interactions. Then, a brief analysis of the Brazilian urbanization model and the implications of it for land distribution and conflict development. Next, a comparison between the treatment offered to collective land conflicts in the Code of Civil Procedure/1973 and the treatment in the new Code. To this purpose, we have analyzed the legislation and some concrete cases (before and after the Code of 2015). From this point on, we discuss the limits and possibilities of conflict mediation in urban conflicts and the necessity of historicize and treat it as a reflection of a new social regulation paradigm. As a case study, we have focused in the conflict of the Izidora Occupations and the judgment of the Order Question that denied the viability of judicial mediation in this case. The event portrays the difficulties in the legal socialization of a new culture. At the end, we have proposed ways to bring mediation closer to the community and institutions as well as the conditions under which mediation can manage urban land conflicts.